Malaysian Employers' Attitudes toward Hiring Persons with Disabilities - Zulfikri, Osman (2003)
Like everyone else, disabled people have natural rights. The rights to be employed, to have better life and income, and together contributing in developing their nation. However, many people with disabilities are still struggling to enter the labor market. Notwithstanding, Malaysian employers are found to be discriminative in hiring disabled workers. Presently, jobs offered to disabled workers are also normally for lower position. The Ministry of National Unity and Social Development through its working group on legislation had drafted a proposed Act to be called the Person with Disabilities Act. However, these federal initiatives, as important as they are, have not changed the way many employers feel about hiring the disableld people. The purpose of this study is to investigate the attitudes and perceptions of Malaysian employers toward hiring people with disabilities. The study postulates, among others, that an organization’s training and development policy can give an idea, if not a total picture, of its attitude towards disabled people. It is acknowledged that policies, being major organizational documents, are usually well thought out prior to publication and enforcement. Hence, the blueprint should enable outsiders to gauge the commitment and conviction an organization’s management has. This should in turn reflect on its overall attitude. On the other hand, an organization unique workplace environment is generally designed and constructed with a certain purpose in mind. The final condition of a working environment depends a lot on physical infrastructure apart from manpower infrastructure. It has been suggested that the intention of the owner, designer and organization had been incorporated at the planning stage. Hence, whether the issue of providing a conducive environment to human in general and unfortunate human specifically should have been forethought. It is realized that the situation and condition of the workplace would also reflect an organization attitude towards disabled people. Lastly, the legal and ethical environment an organization operates in, is indeed influential on its attitude towards disabled people. The study also found that, those surveyed perceived their organizations had been unfair in offering jobs while at the same time do not provide special training programs tailored for disabled workers. On the positive side though, organizations gave the same benefits and salary schemes, equal opportunity for advancement and are socially responsible in term of employment opportunity given to disabled workers. However, employers do not really care about disabled people involvement in nation building! Moreover, organizations seemed to refer ‘normal’ prospective employees, during selection and recruitment, to disabled people. The cross tabulations revealed that the private sector’s employment of disabled workers declined sharply. The three hypotheses were then tested and found that training and development policy and the legal and ethical environment were proven to have significant relationships with employers’ attitude individually. However, an organization unique workplace environment was not. Although the strengths of each relationship were not established the significance of two out of three, are thought to be good for future research and prediction on employers’ attitude. In conclusion, it is proposed that a further research be conducted, to find out the exact nature of the declining trend in hiring disabled workers. Finally, the findings raised the need for a review of existing legal provisions to ensure equal employment opportunity for all.